Re-introducing prize-linked savings products in South Africa through business model innovation - Khayelihle Ludgar Busa Mkhize (Graduate School of Business (GSB), 2024)
The aim of this research study was to determine how business model innovation can be used to re-introduce prize-linked savings (PLS) products in South Africa in the context of the illegalization of FNB's Million-a-Month-Account (MaMa) by the Supreme Court of Appeals ruling in 2008. The study first explores the detailed underlying factors that led to the demise of FNB's MaMa program, beyond the obvious Lotteries Act challenges. Using FNB's Million-a-Month account experience as a case study, a qualitative research study was undertaken, with primary data collected through 10 in-depth semi-structured interviews with financial services experts and regulatory authorities. Content analysis of the data was used to identify themes to address the research questions. Key research findings suggest that the failure of FNB's MaMa program was due to: the ambiguities of the Lotteries Act with regards to prize-linked savings that existed until the ruling by the Supreme Court of Appeal was made in 2008; poor co-operation between government departments towards positive alignment between the regulation of the financial services industry versus the national lottery; and high industry or market concentration in the banking sector that led to lack of innovation and collaboration. A theoretical and practical contribution is made in the form of a comprehensive business model innovation framework for re-introducing PLS products in South Africa, which will provide valuable guidance to practitioners and researchers. As far as could be determined, it is the first academic study to explore prize-linked savings products from a business model innovation perspective